2021
DOI: 10.1016/j.lanepe.2020.100014
|View full text |Cite
|
Sign up to set email alerts
|

Attack rates amongst household members of outpatients with confirmed COVID-19 in Bergen, Norway: A case-ascertained study

Abstract: Background Households studies reflect the natural spread of SARS-CoV-2 in immunologically naive populations with limited preventive measures to control transmission. We hypothesise that seropositivity provides more accurate household attack rates than RT-PCR. Here, we investigated the importance of age in household transmission dynamics. Methods We enroled 112 households (291 participants) in a case-ascertained study in Bergen, Norway from 28th February to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 26 publications
2
67
1
Order By: Relevance
“…Our SAR-estimate of 42.5% for non-VOC viruses is higher than the estimates of around 17 % found in other early reviews (2, 14), but is in accordance with another Norwegian household study from the first wave of the pandemic, which estimated a SAR of 47% based on RT-qPCR and seroconversion (15). Other studies performed in the UK, the Netherlands, and the US in the beginning/middle of 2020 also found similar SARs of 37%-53% (16-18).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our SAR-estimate of 42.5% for non-VOC viruses is higher than the estimates of around 17 % found in other early reviews (2, 14), but is in accordance with another Norwegian household study from the first wave of the pandemic, which estimated a SAR of 47% based on RT-qPCR and seroconversion (15). Other studies performed in the UK, the Netherlands, and the US in the beginning/middle of 2020 also found similar SARs of 37%-53% (16-18).…”
Section: Discussionsupporting
confidence: 88%
“…However, our estimate is in accordance with the 37% found in a prospective study performed in the UK in the beginning of 2020 [12], even though they also included probable secondary cases not confirmed by RT-PCR. A household study from Norway in the spring of 2020 reported a SAR of 47% based on RT-PCR and seroconversion [13]. Similar high SARs were found in the US (53%) and the Netherlands (51% in adults, 35% in children) [14,15].…”
Section: Discussionmentioning
confidence: 62%
“…We collected demographic and clinical data as well as blood samples. Household members of patients who tested positive were included to ensure completeness of the cohort, and their infection was diagnosed by SARS-CoV-2-specific antibodies at 2 months 15 . At 6-month follow-up, the study population available for analysis comprised 312 patients, of whom 247 were home-isolated and 65 were hospitalized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The study population included SARS-CoV-2 RT-PCR-positive patients diagnosed at Bergen Municipality Emergency Clinic and those admitted to the two neighboring city hospitals: Haukeland University Hospital and Haraldsplass Deaconess Hospital. Household contacts of identified patients were invited to participate in the study as secondary cases (seroconverters) or seronegative controls 15 . All registered patients with SARS-CoV-2 were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with a previous meta-analysis which have estimated a secondary attack rate of 16.6% (95% CI, 14.0–19.3%) [ 38 ] and with two register-based studies carried out in Denmark where secondary attack rates between 10%-30% were found [ 11 , 39 ]. However, a Norwegian study found an overall attack rate of 45% in households by use of serology [ 40 ]. We were unable to disentangle the direction of transmission between generations and our design did not allow us to shed light on seroconversion of siblings or other household members who were not the legal parent of the child.…”
Section: Discussionmentioning
confidence: 99%